Peran Bimbingan Konseling Sufistik terhadap Perkembangan Remaja - Laila Nurfadila (UIN Sunan Gunung Djati Bandung, 2023)
This research is motivated by the fact that many youth are not familiar with the world of Sufism, especially with the method of counseling in a Sufi environment. The purpose of this study is to consider the role of Sufi guidance and counseling in the spiritual development of youth. This research used a qualitative type of research with a descriptive-qualitative method. Counseling itself helps individuals to understand and guide themselves, especially in adjusting to school, home and society in general. Counseling itself can also be interpreted as helping individuals to solve life problems to achieve well-being with the help of counseling. The development of adolescent religious souls is also influenced by physical and mental development. Sufi counseling is an effort to provide counseling assistance to individuals or groups in need. The main problem of this research is that this mystical counseling has an effect on the spiritual development of adolescents. Joint scientific research has theoretical and practical uses and benefits. Theoretically, this research is expected to develop insights into mystical guidance for the spiritual development of the younger generation.